2018
DOI: 10.1553/populationyearbook2017s293
|View full text |Cite
|
Sign up to set email alerts
|

The educational gradient of fertility intentions: a meta-analysis of European studies

Abstract: Unlike achieved fertility, fertility intentions are often positively correlated with education. However, the conditions under which such a positive relationship exists are not yet well known. Using 86 pieces of research covering 13 European countries that were published between 1990 and 2011, we assess in a quantitative manner the temporal and cross-country variation in the relationship between educational attainment and reproductive intentions. Because of the sequential nature of reproductive decisions and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 38 publications
1
21
0
4
Order By: Relevance
“…This is in accordance with the result that social capital is a regional phenomenon, see for instance(Beugelsdijk and Van Schaik, 2005) or(Pichler and Wallace, 2007).4 There are many more recent studies focusing on the socioeconomic role of trust, e. g (Stephany, 2019;Testa and Stephany, 2017). or(Freitag and Bauer, 2013).…”
supporting
confidence: 80%
“…This is in accordance with the result that social capital is a regional phenomenon, see for instance(Beugelsdijk and Van Schaik, 2005) or(Pichler and Wallace, 2007).4 There are many more recent studies focusing on the socioeconomic role of trust, e. g (Stephany, 2019;Testa and Stephany, 2017). or(Freitag and Bauer, 2013).…”
supporting
confidence: 80%
“…Childbearing decisions continue to be the subject of intensive research, especially in the context of low fertility countries, where attention is drawn to the factors that limit these decisions (e.g., Billingsley & Ferrarini, 2014;Guzzo & Hayford, 2020;Philipov et al, 2006;Testa & Stephany, 2018). While numerous factors have been examined in this respect, we focus on three major areas, which were vividly discussed in the pre-pandemic era and which might become even more important with the COVID-19 outbreak.…”
Section: Fertility Choices In the Pre-pandemic Eramentioning
confidence: 99%
“…Finally, women who have obtained post-secondary higher education (i.e., university degree) were less likely to decrease their desired number of children. This finding might be explained in light of a recent meta-analysis of European fertility intention studies which found a positive association between education and intentions to reach normative family size [52]. Another explanation to these findings may be related to the greater human capital that more educated women may have, which might help them preserve their initial fertility intentions when faced with the reality and burden which might be associated with having a child.…”
Section: Discussionmentioning
confidence: 94%